Planning and management of provision of essential medicines as part of health services at the public municipal health units in the province of Zamboanga del Sur, Philippines - Sangey, Kuenzang Lham (2004)
World Health Organization Policy odf Department of Essential Drugs noted low access to essential medicines and high prevalence of both the communicable and non-communicable diseases in the Philippines compared to other Asian countries namely: Thailand and Vietnam...According to economic theorists (Gertler and Hammer 1997), "governments in developed and developing countries provide health care services in many ways since the health is, in many respects, a public good". One of the common way in which the government is involved in the health sector is through public municipal health programs...[19 other paragraphs]
"October 2007."
Thesis ( M.S. Urban & Regional Planning: Regional Development Planning)--University of the Philippines Diliman.
Keywords: Transportation medicine -- Philippines -- Margosatubig (Zamboanga del Sur).; Transportation medicine -- Philippines -- Labangan (Zamboanga del Sur).; Transportation medicine -- Philippines -- Lapuyan (Zamboanga del Sur).; Public health -- Philippines -- Margosatubig (Zamboanga del Sur).; Public health -- Philippines -- Labangan(Zamboanga del Sur).; Public health -- Philippines -- Lapuyan(Zamboanga del Sur).